2011
DOI: 10.4236/jst.2011.14016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Humidity Sensing Investigations of Nanostructured ZnSnO<sub>3</sub>

Abstract: In this paper zinc stannate (ZnSnO 3 ) nanoparticles was synthesized by a chemical precipitation method. The synthesized samples were characterized using X-ray powder diffraction (XRD), Differential scanning calorimetry (DSC) and UV-Visible absorption spectroscopy. Sensing material was made as pellet by hydraulic press machine under uniform pressure of 616 MPa. Then the material was annealed at 600˚C. Surface morphologies of the samples were analyzed using Scanning electron microscopy (SEM) for pellet of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The appearance of the preferential diffraction peak, assigned to the plane (002), indicates that the film growth is achieved along the axis c of the hexagonal structure normal to the substrate surface Fig.7, this is good concordance with the SEM observation for (Lehraki et al) [20] Zinc stannate (ZnSnO 3 ) has either structure perovske, according to results XRD the structure was perovske which shows almost all the particles are spherical in shape leaving some space between them Fig. 10, this is good concordance with the SEM observation for (Singh et al) [21].…”
Section: Resultssupporting
confidence: 82%
“…The appearance of the preferential diffraction peak, assigned to the plane (002), indicates that the film growth is achieved along the axis c of the hexagonal structure normal to the substrate surface Fig.7, this is good concordance with the SEM observation for (Lehraki et al) [20] Zinc stannate (ZnSnO 3 ) has either structure perovske, according to results XRD the structure was perovske which shows almost all the particles are spherical in shape leaving some space between them Fig. 10, this is good concordance with the SEM observation for (Singh et al) [21].…”
Section: Resultssupporting
confidence: 82%
“…Compared to the above values, the rGO-SnO 2 nanoparticles have a better sensitivity factor and faster response and recovery times. The fast response of the sensor is also attributed to the large quantity of hydrophilic quaternary SnO 2 groups in the rGO [47], which interact quickly with water molecules, while the rapid recovery speed is due not only to the separation of sensitive points in the framework, but also to the porosity, which is characteristic of rGO-SnO 2 [48,49]. …”
Section: Resultsmentioning
confidence: 99%
“…Kovacheva and Petrov [24] showed that ZnSnO 3 cannot adopt a perovskite structure under normal conditions, since the ionic radius of Zn 2 þ is too small. SnO 2 -ZnO materials have been synthesized by various preparation methods, such as solid-state reactions [5], chemical precipitation [25], spray pyrolysis [26], hydrothermal [20], and sol-gel method [27].…”
Section: Introductionmentioning
confidence: 99%